Analyses of Deoxyribonucleic Acid of Neisseria caviae and other Neisseria - LaMacchia, Elizabeth H. (1966)
LaMacchia, Elizabeth H. (University of Maryland, College Park), and Michael J. Pelczar, Jr. Analyses of deoxyribonucleic acid of Neisseria caviae and other Neisseria. J. Bacteriol. 91:514–516. 1966.—The base composition of deoxyribonucleate preparations extracted from 11 strains of Neisseria caviae, expressed in terms of mole per cent guanine plus cytosine ranged from 47.7 to 50.4, with an average of 49.2. This compared closely with the values obtained for DNA from two strains of N. perflava, which were 49.2 and 50.5%, as well as with published values for most other Neisseria species. The values obtained for five strains of N. catarrhalis, however, ranged from 42.3 to 45.7%. These results suggest that N. caviae may be more closely related to Neisseria spp. other than N. catarrhalis.